Long-Term Impacts of Non-Sustainable Tourism and Urban Development in Small Tropical Islands Coastal Habitats in a Changing Climate: Lessons Learned from Puerto Rico - Delgado, Edwin A. Hernández-; Ramos-Scharrón, Carlos E.; Guerrero-Pérez, Carmen R.; Lucking, Mary Ann; Laureano, Ricardo; Méndez-Lázaro, Pablo A.; Meléndez-Díaz, Joel O. (IntechOpen, 2012)
None